2020
DOI: 10.1016/j.celrep.2020.107897
|View full text |Cite
|
Sign up to set email alerts
|

A Patient-Derived Cell Atlas Informs Precision Targeting of Glioblastoma

Abstract: Highlights d A resource of 100 pharmacologically characterized patientderived glioblastoma lines d Integrated analyses define associations between drug response, pathways, and mutations d The response to proteasome inhibitors is linked to TP53 and CDKN2A/B aberrations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 75 publications
0
68
0
Order By: Relevance
“…In summary, these results complementing the distinct advantages of patient-derived 2D and 3D models present a novel workflow for screening small groups of drugs with the potential for a more personalized approach in the treatment of recurrent glioblastoma. Moreover, it is possible to scale up this process further to include additional drugs that also shown promise in the clinical trial setup (e.g., regorafenib [ 128 ], and other Phase II-IV clinical trials drugs as recently reviewed by Cruz DaSilva et al [ 129 ]) as well as drug candidates identified in large scale screenings using 2D cultures of patient-derived cells [ 130 ], which have not been yet tested in 3D GBO models.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, these results complementing the distinct advantages of patient-derived 2D and 3D models present a novel workflow for screening small groups of drugs with the potential for a more personalized approach in the treatment of recurrent glioblastoma. Moreover, it is possible to scale up this process further to include additional drugs that also shown promise in the clinical trial setup (e.g., regorafenib [ 128 ], and other Phase II-IV clinical trials drugs as recently reviewed by Cruz DaSilva et al [ 129 ]) as well as drug candidates identified in large scale screenings using 2D cultures of patient-derived cells [ 130 ], which have not been yet tested in 3D GBO models.…”
Section: Discussionmentioning
confidence: 99%
“…Mutually exclusive expression can be observed as genetic alterations [34, 35, 36, 37] and negative correlations [38, 39] between two specific genes. Genetic alterations lead to protein production because mutually exclusive gene pairs might be amplified in different cell populations [34].…”
Section: Methodsmentioning
confidence: 99%
“…A superior alternative to these permanent cells is patient-derived cell lines in low passages. Published biobanks reflect all kinds of molecular subtypes of glioblastoma [ 174 , 175 , 176 , 177 ]. If the molecular status of the primary tumor is known and the corresponding clinical patient data are available, the correspondingly derived cell lines are of particular value for preclinical studies.…”
Section: Preclinical Models To Study Glutamate Interaction and Tumor-associated Epilepsymentioning
confidence: 99%